TerraceM-2: A Matlab® Interface for Mapping and Modeling Marine and Lacustrine Terraces - Jara-Muñoz, Julius; Melnick, Daniel; Pedoja, Kevin; Strecker, Manfred R. (Frontiers in Earth Science, 2019)
The morphology of marine and lacustrine terraces has been largely used to measure past sea- and lake-level positions and estimate vertical deformation in a wealth of studies focused on climate and tectonic processes. To obtain accurate morphometric assessments of terrace morphology we present TerraceM-2, an improved version of our Matlab® graphic-user interface that provides new methodologies for morphometric analyses as well as landscape evolution and fault-dislocation modeling. The new version includes novel routines to map the elevation and spatial distribution of terraces, to model their formation and evolution, and to estimate fault-slip rates from terrace deformation patterns. TerraceM-2 has significantly improves its processing speed and mapping capabilities, and includes separate functions for developing customized workflows beyond the graphic-user interface. We illustrate these new mapping and modeling capabilities with three examples: mapping lacustrine shorelines in the Dead Sea to estimate deformation across the Dead Sea Fault, landscape evolution modeling to estimate a history of uplift rates in southern Peru, and dislocation modeling of deformed marine terraces in California. These examples also illustrate the need to use topographic data of different resolutions. The new modeling and mapping routines of TerraceM-2 highlight the advantages of an integrated joint mapping and modeling approach to improve the efficiency and precision of coastal terrace metrics in both marine and lacustrine environments.